Preparation of magnetic solvent-free carbon nanotube/Fe3O4 nanofluid sizing agent to enhance thermal conductivity and interfacial properties of carbon fiber composites. (3rd May 2023) - Li, Jun; Jiang, Na; Cheng, Chunxia; Quan, Guipeng; Feng, Hengyu; Li, Weiwen; Xiao, Linghan; Ao, Yuhui
Abstract: A solvent-free multi-wall carbon nanotubes (MWCNTs) @Fe3 O4 nanofluid (MFNF) was prepared to modify the water-based epoxy (WEP) sizing agent to address the undesirable interfacial properties and thermal conductivity (TC) of carbon fiber reinforced polymers (CFRPs). The results of the study showed that the performance of CFRPs with MFNF content of 2% was significantly improved, with ILSS and bending strength increased by 21.69% and 39.51%, respectively. This is attributed to MFNF leads to a strong mechanical interlock between CF and epoxy resin, which improves the mechanical properties. In addition, the TC was improved by 112.23%. This is partly due to the excellent TC possessed by MWCNTs and partly due to the orientation of the MFNF in thermal conductivity through the use of a magnetic field, creating a continuous thermal path at the interface, which facilitates phonon propagation. In conclusion, this method provides a new strategy for the preparation of multifunctional CFRPs. Graphical abstract: Image 1 Highlights: Preparation of magnetic carbon nanotube nanofluids to address agglomeration of carbon nanotubes in sizing agents. Orientation of nanofluids on carbon fibres by magnetic fields improves the thermal conductivity of composites. Carbon nanotube nanofluids leads to astrong mechanical interlock between carbon fibres and epoxy resin.